Integration of precision agriculture strategies to improve cocoa productivity and quality - Tee, Yei Kheng (2019)
Cocoa industry faces challenges such as high input costs and low cocoa productivity despite pest and disease problem. Currently, cocoa is managed conventionally using labour in farm management, however, more effective production systems need to be identified to increase competitiveness of cocoa supply chain and to sustain high demand in the grinding industry. Thus, precision strategies are built upon modern system approaches which aim to transform the cocoa production system towards low input, high efficiency and sustainable cocoa production. So far, there is no research focus on applying precision technology in the cocoa production chain in Malaysia. In this research, the studies were designed at three different stages of cocoa production system, from young cocoa seedlings at the nursery to mature cocoa trees and finally cocoa bean quality, targeting the issues faced by the cocoa industry at each of the production stages through precision cocoa management. Remote sensing was applied to determine the reflectance in young cocoa seedlings subjected to N and K deficiency and the study was supported with physical (height, girth and leaf area) and physiological (plant net photosynthesis, transpiration rate and chlorophyll content) data as plants developed. A total of 72 grafted cocoa seedlings with clone MCBC10 were planted in the greenhouse. The seedlings were six months old after sowing with three treatments (T1: complete nutrients of nitrogen, phosphorus and potassium; T2: nitrogen deficiency; T3: potassium deficiency) arranged in a randomized complete block design. From this study, hyperspectral reflectance showed that plants with nutrient deficiency had higher reflectance at the visible range of 550 nm while plants with complete fertilizers achieved the highest peak of reflectance in the near-infrared 700-2500 nm ranges. Cocoa seedlings with nitrogen and potassium deficiency showed a shift in the red edge with greater reflectance at 675-750 nm. Nitrogen deficiency had the most pronounced effects on growth, net photosynthesis, transpiration rate and chlorophyll content at young cocoa seedlings. The output of the study was able to detect seedlings with nutrient deficiency at early stages in order to ensure seedlings planted by the smallholders are in healthy condition. A multivariate geospatial approach was used to quantify the spatial and temporal variability of soil properties, cocoa pod borer infestation rate and cocoa fresh bean weight at two different commercial planting systems of mature cocoa. From the study, precision cocoa farm management helped to increase crop yield by 58.8 and 51.1% at cocoa-gliricidia and cocoa-coconut, respectively, might be due to the effective pest control in the critical zone and site-specific fertilization, especially during high peak harvesting season of cocoa. During harvesting, bean quality is an important factor that influences for higher pricing and the quality is affected by the maturity stages during harvesting. Hence, this study was carried out to determine the optimum harvest period for cocoa using a non-destructive method of multi-parametric sensor. From this study, flavonol accumulated as cacao pods developed, however, chlorophyll and nitrogen balance index declined as pods reached maturity at four months after pod emergence. Post-harvest bean quality tests indicated that pods harvested at the mature stage of four months after pod emergence met the standards certified by the Malaysian Standard and the bean quality is as good as beans harvested at the ripe stage of five months after pod emergence.